Assessing meaning-dimension quality in consecutive interpreting training. (4th March 2018) - Ouyang, Qianhua
ABSTRACT: This research aims to bring intertextual analysis under the framework of systemic functional linguistics (SFL) into the assessment of meaning transfer in classroom consecutive interpreting performance. An assessment model is constructed to investigate meaning transfer through both contextual-level register analysis and textual-level lexicogrammatical analysis by associating principal interpreting quality assessment criteria with respective meaning streams of SFL; namely, accuracy with ideational meaning, appropriateness with interpersonal meaning and coherence with textual meaning. To test the proposed model's applicability and effectiveness, it was applied to assess 10 students' interpretations between Chinese and English that were randomly selected from a corpus of interpretations collected in two quasi-exam sessions. The evidence collected from implementation of the model shows that the SFL-backed approach broadens the spectrum of meaning assessment in interpreting by highlighting the often-neglected interpersonal dynamics of language use in interpreting; the study yields objective and systematic assessment results supported by concrete evidence, and indicates sources of and reasons for interpreting problems, which provide useful insights for interpreter trainers when designing their courses.